2021
DOI: 10.17816/cp66
|View full text |Cite
|
Sign up to set email alerts
|

Immunoinflammatory Profile in Patients with Episodic and Continuous Paranoid Schizophrenia

Abstract: Introduction. Associations of disturbances in innate and adaptive immunity during the clinical course of schizophrenia have been found in a number of studies. Yet, the relationship of immune parameters and systemic inflammation in relation to the clinical course of the disease and its prognosis, remains poorly understood, which highlights an interesting topic for further research. The goal of this study was to research the immuno-inflammatory changes in patients with clinical continuous and episodic paranoid s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…In a clinical sense, proinflammatory cytokines-as some of the pathogenesis components-play an important role in clinical polymorphism and the course of schizophrenia through reactivity mechanisms. Malashenkova et al [56] have reported that episodic schizophrenia and continuous schizophrenia have signs of systemic inflammation. At the same time, the continuous course of schizophrenia is characterized mainly by chronic activation of the humoral response, whereas the episodic one by some activation of cell-mediated immunity.…”
Section: Discussionmentioning
confidence: 99%
“…In a clinical sense, proinflammatory cytokines-as some of the pathogenesis components-play an important role in clinical polymorphism and the course of schizophrenia through reactivity mechanisms. Malashenkova et al [56] have reported that episodic schizophrenia and continuous schizophrenia have signs of systemic inflammation. At the same time, the continuous course of schizophrenia is characterized mainly by chronic activation of the humoral response, whereas the episodic one by some activation of cell-mediated immunity.…”
Section: Discussionmentioning
confidence: 99%
“…The literature and our data confirm the fact that patients with schizophrenia show the signs of systemic inflammation, which are most intensive in the first episode of the disease and in exacerbations. In disease exacerbation, the levels of pro-inflammatory cytokines IL-8, TNF-α, and CRP, an acute-phase protein, increase [18][19][20]. A high CRP level has been also shown to be associated with a more severe course of psychosis in schizophrenia and subsequent cognitive function decline [18,21].…”
Section: Discussionmentioning
confidence: 99%
“…Table 4 shows feature importance ranking using XGBoost classifier, having the second values of ROC AUC and ACC, high or moderate stability of the classification results (ROC AUC -0.68±0.21; ACC -0.75±0. 19).…”
Section: Roc Auc (σ)mentioning
confidence: 99%
“…Numerous clinical, postmortem, biomedical, genetic and experimental studies, including cell and animal models, have shown that schizophrenia is accompanied by neuroinflammation and systemic immune disorders [4,5,6]. According to the results of large genome-wide association studies (GWAS), single-nucleotide polymorphisms in genes regulating the functions of the immune system have significant associations with schizophrenia risk [7,8]. Patients with psychotic episode have increased levels of inflammation markers in the cerebrospinal fluid and systemic circulation, and an increased expression of proteins involved in the immune response and inflammation in the prefrontal cortex [4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of large genome-wide association studies (GWAS), single-nucleotide polymorphisms in genes regulating the functions of the immune system have significant associations with schizophrenia risk [7,8]. Patients with psychotic episode have increased levels of inflammation markers in the cerebrospinal fluid and systemic circulation, and an increased expression of proteins involved in the immune response and inflammation in the prefrontal cortex [4][5][6][7]. According to indirect evidence, schizophrenia associated with neuroinflammation can account for up to 40% of cases, but more convincing studies are needed [2].…”
Section: Discussionmentioning
confidence: 99%